Assessment of pollen reward and pollen availability in Solanum stramoniifolium and Solanum paniculatum for buzz‐pollinating carpenter bees. (18th October 2013) - Burkart, A.; Schlindwein, C.; Lunau, K.; Dafni, A.
Abstract The two widespread tropical Solanum species S. paniculatum and S. stramoniifolium are highly dependent on the visits of large bees that pollinate the flowers while buzzing them. Both Solanum species do not offer nectar reward; the rewarding of bees is thus solely dependent on the availability of pollen. Flower visitors are unable to visually assess the amount of pollen, because the pollen is hidden in poricidal anthers. In this study we ask whether and how the amount of pollen determines the attractiveness of flowers for bees. The number of pollen grains in anthers of S. stramoniifolium was seven times higher than in S. paniculatum. By contrast, the handling time per five flowers for carpenter bees visiting S. paniculatum was 3.5 times shorter than of those visiting S. stramoniifolium. As a result foraging carpenter bees collected a similar number of pollen grains per unit time on flowers of both species. Experimental manipulation of pollen availability by gluing the anther pores showed that the carpenter bees were unable to detect the availability of pollen by means of chemical cues before landing and without buzzing. Our study shows that the efficiency of pollen collecting on S. paniculatum is based on large inflorescences with short between‐flower search times and short handling time of individual flowers, whereas that of S. stramoniifolium relies on a large amount of pollen per flower. Interestingly, large carpenter bees are able to adjust their foraging behaviour to drastically different strategies of pollen reward in otherwise very similar plant species.